SWOT-analysis of practice of the Kyiv region ambulatory care facilities that provide cardiac care to the population - Ivaniuk , Anatoliy; Kaniura, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2023)
the aim of study to consider the possibility of using the SWOT-analysis in assessing the practice of the Kiev region ambulatory care facilities (ACF) that provide cardiac care to the population. Analytical method of mechanisms research and capabilities of the SWOT-method analysis realization in assessing health care facilities practice with the systematical approach usage. Based on the SWOT-analysis, the article reveals the advantages and disadvantages of Kiev Region ACF that provide cardiac care, as well as points to risks and capabilities in their practices. It presents that the SWOT method analysis matrix in relation to health care institutions includes all the information on the diagnostic and technologies availability, ACF structure and composition, medical personnel training level. Through the SWOT-analysis, the existing problems in the cardiac patient health care of the region were revealed. The basic principles of ACF organization are determined, and the key point is public-private partnership mechanisms implementation in the health care. The SWOT-analysis is an effective line of research in the system of healthcare environments. The SWOT-analysis implementation provides consideration of all potential factors that may affect the quality level of health services provided and establishes the directions of reforming of Kiev region ACF that provide cardiac care to the population.